The power of humour to unite and divide: a case study of design coordination meetings in construction. Issue 1 (2nd January 2020) - Ponton, Hazel; Osborne, Allan; Thompson, Neill; Greenwood, David
Abstract: Design coordination meetings are the formal discussion venues that support interdisciplinary group interaction during the construction process. Social behaviour needs to be recognized, understood, and evaluated by group members if meetings are to be productive. The role of humour during the practice of coordinating building design has not previously been studied. A non-participant observation method was used to collect qualitative data from consecutive contractor-led design team meetings during a live building project. Using a 360° panoramic video-recording camera, episodes of humour were captured and collated into packets of rich data. These packets were then organized, structured, and analysed using NVivo computer-assisted qualitative data analysis software. The results of the analysis showed that instances of humour do not happen at random but at specific times when they performed distinct functions to facilitate the design coordination process. One notable example was the role of humour in helping to form a cohesive team that was able to manage conflict successfully and thus engender a positive cultural environment. The inclusive findings of the study have demonstrated that humour is a functional aspect of group dynamics during the coordination of design in construction that can influence social interaction and task-related performance.